2010
DOI: 10.1073/pnas.1002418107
|View full text |Cite
|
Sign up to set email alerts
|

Optical activation of lateral amygdala pyramidal cells instructs associative fear learning

Abstract: Humans and animals can learn that specific sensory cues in the environment predict aversive events through a form of associative learning termed fear conditioning. This learning occurs when the sensory cues are paired with an aversive event occuring in close temporal proximity. Activation of lateral amygdala (LA) pyramidal neurons by aversive stimuli is thought to drive the formation of these associative fear memories; yet, there have been no direct tests of this hypothesis. Here we demonstrate that viral-targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
207
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 58 publications
9
207
3
2
Order By: Relevance
“…Previous studies show that activation of the lateral amygdala is involved in fear learning (Johansen et al, 2010). Here we show that activating opto-β 2 AR in the CaMKIIα+ neurons of the BLA had no effect on CPA or RTPA.…”
Section: Discussioncontrasting
confidence: 41%
“…Previous studies show that activation of the lateral amygdala is involved in fear learning (Johansen et al, 2010). Here we show that activating opto-β 2 AR in the CaMKIIα+ neurons of the BLA had no effect on CPA or RTPA.…”
Section: Discussioncontrasting
confidence: 41%
“…Briefly, activation of LA neurons induces unconditioned freezing 70 . These cells develop robust responses to shock-predictive cues, corresponding to freezing behavior when the cues are presented 71 projecting directly to the CeM shows evidence of potentiation following fear conditioning, and photoinhibition of these neurons inhibits the acquisition of the fear association 63 .…”
Section: Microcircuits and Interactions Among Nodesmentioning
confidence: 99%
“…Examples abound in humans that highlight the dramatic instances in which distorted memories of crime scenes, childhood events, and traumatic experiences-often recalled under interrogation in the court of law or during psychotherapy sessions-disrupt both individual well-being and modern jurisprudence (Loftus 2003;Schacter and Loftus 2013). having never been naturally, or exogenously, presented (Johansen et al 2010). Another study demonstrated that an activated population of piriform cortex neurons, when paired with rewards or shocks, could drive the associated appetitive or aversive behavioral output upon stimulation of the same neurons (Choi et al 2011).…”
Section: Generating False Memories Based On Memory Engram Cellsmentioning
confidence: 99%